2002
DOI: 10.1007/s00280-002-0460-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of keratinocyte growth factor on tumour growth and small intestinal mucositis after chemotherapy in the rat with breast cancer

Abstract: We conclude that KGF had a modest effect on intestinal growth prior to chemotherapy. It did not protect the gut from mucositis, nor did it worsen morphometry. It reduced tumour size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…8,23,24 This tumor is specific to the DA rat. Tumor-bearing animals were used in this study to ensure that palifermin did not promote tumor growth or interfere with the cytotoxicity of irinotecan.…”
Section: Passage Of Tumormentioning
confidence: 99%
See 2 more Smart Citations
“…8,23,24 This tumor is specific to the DA rat. Tumor-bearing animals were used in this study to ensure that palifermin did not promote tumor growth or interfere with the cytotoxicity of irinotecan.…”
Section: Passage Of Tumormentioning
confidence: 99%
“…The method used to stain for apoptosis was performed using the In Situ Cell Death Detection Kit AP (Roche, Mannheim, Germany) and has been described elsewhere. 2,8,[23][24][25] Briefly, slides were dewaxed and rehydrated through graded ethanols prior to immersion in a 0.1% TX-100 in 0.1% (w/v) sodium citrate buffer solution for 8 min at room temperature. After 2 washes in PBS, slides were placed in a TUNEL buffer solution (150 mM Tris, 0.7M NaCaCo, 10 mM CoCL 2 , 10% BSA, sterile H 2 0) for 10 min at room temperature.…”
Section: Apoptosis Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All rats received breast cancer inoculum as described previously. 49,50 Briefly, mammary adenocarcinoma tumors syngeneic with the DA rat were diced, homogenized and filtered through sterile gauze. A viable cell count was conducted using 0.4% w/v trypan blue before 150 μl of cells were implanted subcutaneously into both right and left flanks of the rat at a concentration of 2.0 × 10 7 cells/mL.…”
Section: Experimental Designmentioning
confidence: 99%
“…Data from animal models 24,25 showed that KGF treatment is effective in the prevention of intestinal mucositis. KGF is produced by mesenchymal cells and is a member of the fibroblast growth factor (FGF) superfamily.…”
Section: Discussionmentioning
confidence: 99%